2012
DOI: 10.1155/2012/246874
|View full text |Cite
|
Sign up to set email alerts
|

Desert Dust Outbreaks over Mediterranean Basin: A Modeling, Observational, and Synoptic Analysis Approach

Abstract: Dust intrusions from African desert regions have an impact on the Mediterranean Basin (MB), as they cause an anomalous increase of aerosol concentrations in the tropospheric column and often an increase of particulate matter at the ground level. To estimate the Saharan dust contribution to PM 10 , a significant dust intrusion event that occurred in June 2006 is investigated, joining numerical simulations and specific measurements. As a first step, a synoptic analysis of this episode is performed. Such analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…1) that the strong winds (10-15 m s À1 ) over the Thar desert are the main reason for the uplift and transport of the dust plumes towards central IGB, also supported by the enhanced advection and boundary-layer height due to high temperature. The air temperature, humidity, soil moisture, vegetation cover, topography, erodibility, surface winds, turbulence and buoyancy are crucial parameters for the dust erosion and life cycle (Shao et al, 2011;Calastrini et al, 2012;Cavazos-Guerra and Todd, 2012), as was also shown for the dust event on 20 April . The slight difference in the atmospheric circulation during the three dust events (Fig.…”
Section: Satellite Monitoring Of the Dust Storms Over Igbmentioning
confidence: 73%
“…1) that the strong winds (10-15 m s À1 ) over the Thar desert are the main reason for the uplift and transport of the dust plumes towards central IGB, also supported by the enhanced advection and boundary-layer height due to high temperature. The air temperature, humidity, soil moisture, vegetation cover, topography, erodibility, surface winds, turbulence and buoyancy are crucial parameters for the dust erosion and life cycle (Shao et al, 2011;Calastrini et al, 2012;Cavazos-Guerra and Todd, 2012), as was also shown for the dust event on 20 April . The slight difference in the atmospheric circulation during the three dust events (Fig.…”
Section: Satellite Monitoring Of the Dust Storms Over Igbmentioning
confidence: 73%
“…Results are shown, as monthly averages, in Fig. 3, where a clear seasonal trend may be observed: during winter~80% of K is soluble and quite high EFs are observed, while a lower solubility and a lower enrichment are observed in summer (the very low value in June for both EF and solubility has to be ascribed to a strong Saharan dust episode, which lasted several days (Nava et al, 2012;Calastrini et al, 2012)). A high correlation between K and K + (r 2 = 0.94) is indeed observed during winter (Fig.…”
Section: Daily Data: Pm10 Concentration and Compositionmentioning
confidence: 93%
“…For this purpose, a maximum covariance analysis (MCA) (von Storch and Zwiers, 1999) is applied to the daily anomalies of AOD (GOCART and MODIS) and MERRA air temperature at 850 hPa (T850) in the Mediterranean basin (10 • W-40 • E, 30 • N-45 • N). T850 well portrays Saharan air masses, which are characterized by a sharp vertical profile with very warm lower levels contrasting colder air aloft (Lavaysse et al, 2009;Calastrini et al, 2012). Thus, T850 is a natural marker to identify such air masses and stratify them among air masses coming from the Atlantic Ocean, which are characterized by smoother vertical temperature gradient.…”
Section: Methodsmentioning
confidence: 99%